GPS‐Based LEO Orbits Referenced to the Earth's Center of Mass. Issue 2 (31st January 2020) - Couhert, Alexandre; Delong, Nicolas; Ait‐Lakbir, Hanane; Mercier, Flavien
Abstract: Global Navigation Satellite System satellite clock solutions of the International Global Navigation Satellite System Service are aligned to the International Terrestrial Reference Frame origin. This strategy is not sufficient to model correctly the Low Earth Orbit (LEO) Global Positioning System (GPS) measurements, because the geocenter motion is not taken into account for the ground station positions in these solutions. In order to be consistent with the dynamic motion of a LEO satellite, and also with the other measurement systems where the geocenter motion can be modeled (e.g., Satellite Laser Ranging and Doppler Orbitography and Radiopositioning Integrated by Satellite), it is necessary to take into account or mitigate the miscentering effect of the constellation solution. In this paper, we use a parametric model representing the reference network translations, and this model can be adjusted in the OSTM/Jason‐2 and Jason‐3 LEO satellites orbit determination. Plain Language Summary: The ever‐changing fluid mass (oceans, continental water, snow, atmosphere, …) redistributions on the Earth's surface give rise to a motion of the deformable terrestrial crust, with respect to the center‐of‐mass (CM) of the Earth. This motion is called "geocenter motion." Even though the expected amplitude is smaller than the size of a cherry, it is now necessary to take into account its perturbing effect on the modeling of ground station observations (tied to the crust), used to observe the natural orbital motion of the satellites about CM (according to Newton's laws). Indeed, Global Positioning System (GPS) measurement models and derived products are currently aligned to the International Terrestrial Reference Frame origin (which is referenced to the crust), instead of CM. In this paper, we derive a model to obtain CM‐centered GPS data. This improves the determination of GPS‐based low‐Earth satellite orbits and helps to provide insight into the temporal variations of the geocenter motion. Key Points: Independent geocenter coordinates were derived using GPS data and the OSTM/Jason‐2 satellite A GPS satellite clock correction model was derived to improve the centering of IGS GPS products The advent of fixing GPS ambiguities for LEO satellites increases the sensitivity of the orbit solutions to geocenter errors